Tonaliteter: Om struktur og betydning i Ib Nørholms symfonier og om tonalitet som fænomen og begreb - Andersen, Mogens (Danish Yearbook of Musicology, 1996)
Tonalities. About structure and meaning in Ib Nørholm’s symphonies, and on tonality as a phenomenon and concept A great variety of tonality types is a prominent stylistic feature in Ib Nørholm’s symphonies. Through analyses based mainly on auditive perception, it is shown how tonality serves both the building up of formal entities and, with reference to textual and programmatic content, the establishhing of extramusical meaning. The development from the stylistic diversity of the second symphony to the more unified modes of expression in the later works includes the integration of tonal techniques. These phenomena are exemplified by time indications to the cd recordings of the works. For the analyses, semiologically based principles are put to use, which are explicated in the second part of the article, the perspective of which is indicated by its heading tonality as phenomenon and concept. The interrelationship of structure and meaning is the subject of the third part of the article, focussing on the aspect of tonality, understood in its broad sense as specific pitch relationships.